Methodological Aspects for Preclinical Evaluation of Gadolinium Presence in Brain Tissue: Critical Appraisal and Suggestions for Harmonization—A Joint Initiative. Issue 9 (September 2018) - Robert, Philippe; Frenzel, Thomas; Factor, Cécile; Jost, Gregor; Rasschaert, Marlène; Schuetz, Gunnar; Fretellier, Nathalie; Boyken, Janina; Idée, Jean-Marc; Pietsch, Hubertus
Abstract : Abstract: Gadolinium (Gd)-based contrast agents (GBCAs) are pharmaceuticals that have been approved for 30 years and used daily in millions of patients worldwide. Their clinical benefits are indisputable. Recently, unexpected long-term presence of Gd in the brain has been reported by numerous retrospective clinical studies and confirmed in preclinical models particularly after linear GBCA (L-GBCA) compared with macrocyclic GBCA (M-GBCA). Even if no clinical consequences of Gd presence in brain tissue has been demonstrated so far, in-depth investigations on potential toxicological consequences and the fate of Gd in the body remain crucial to potentially adapt the clinical use of GBCAs, as done during the nephrogenic systemic fibrosis crisis. Preclinical models are instrumental in the understanding of the mechanism of action as well as the potential safety consequences. However, such models may be associated with risks of biases, often related to the protocol design. Selection of adequate terminology is also crucial. This review of the literature intends to summarize and critically discuss the main methodological aspects for accurate design and translational character of preclinical studies.